HUBUNGAN KECEPATAN DENGAN KEMAMPUAN DRIBBLING ATLET BOLABASKET PUTERA CLUB NEO CLACH BUKITTINGGI - Hendri Neldi (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
Problem in this research that is decreasing achievement of athlete of club NEO Clach Bukittinggi, as for research purpose is to know the relation of speed and hand eye coordination to dribbling ability of club basketball athlete of NEO CLACH Bukittinggi. The method of this research is correlation method. The population of this study is all athletes Bolabasket NEO Clach Bukittinggi amounted to 14 people, sampling in this study was done by total sampling technique. So in this study are sampled is 14 people athletes who follow the training of club bolabasket NEO Clach Bukittinggi. This research was conducted in January 2018, while the research place was conducted in SMA 4 N Bukittinggi. Speed ​​data with a 30-meter speed test, eye-hand coordination data of the Neo Clach Bukititinggi basketball athlete, was taken using a throw ball test to the wall and dribbling ability data with a dribbling zig-zag ability test.The result of data analysis shows that: (1). Speed ​​has a significant relationship to dribbling ability, this is indicated by the results obtained is tcount 2.03> ttabel 1.76 (2). Eye Coordination has a significant relationship to dribbling ability, this is indicated by the result obtained that is tcount 3.48> ttabel 1.76 (3). There is a significant joint relationship between speed and hand-eye coordination with dribbling ability. Obtained Fcount 8.97> Ftable 3.35, with the value R = 0.736 obtained R2 = 0.542, while the contribution is 54.2%.